2002
DOI: 10.1212/wnl.58.9.1338
|View full text |Cite
|
Sign up to set email alerts
|

Resection of the lesion in patients with hypothalamic hamartomas and catastrophic epilepsy

Abstract: Resection can alleviate both the seizures and the behavioral and cognitive abnormalities of hypothalamic hamartomas, but complications are frequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
186
0
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(195 citation statements)
references
References 33 publications
1
186
0
8
Order By: Relevance
“…These results were later replicated at the Barrow Neurological Institute. 23 In 2002, Palmini et al 27 reported on 13 patients who underwent surgery for HHs from 3 centers, 12 using a frontotemporal approach and 1 using an endoscopic approach. Delalande and Fohlen 9 reported on 17 patients in 2003 who underwent surgery for HH (14 transsylvian and 9 endoscopic approaches).…”
Section: The Royal Children's Hospital Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…These results were later replicated at the Barrow Neurological Institute. 23 In 2002, Palmini et al 27 reported on 13 patients who underwent surgery for HHs from 3 centers, 12 using a frontotemporal approach and 1 using an endoscopic approach. Delalande and Fohlen 9 reported on 17 patients in 2003 who underwent surgery for HH (14 transsylvian and 9 endoscopic approaches).…”
Section: The Royal Children's Hospital Experiencementioning
confidence: 99%
“…9, 27 Rekate et al 29 reported the early outcome of 44 patients with normal-sized ventricles who underwent endoscopic surgery. Fourteen patients had complete endoscopic removal of the HH, and there was total control of seizures in 13 of these patients.…”
Section: The Endoscopic Approachmentioning
confidence: 99%
“…The hypothesis of an intrinsic epileptogenesis of HH gained impetus after the stereo-EEG demonstration of ictal onsets originating from the hypothalamic lesion, 32 and was further corroborated by subsequent reports showing production of typical gelastic seizures by depth electrode stimulation, ictal SPECT studies demonstrating HH hyperperfusion, and interictal spike source analysis. 4,9,11,12,16,21,22,26,35,45 The epileptogenic activity of HHs has been recently demonstrated at the cellular level: detailed electrophysiological analysis of slices taken from surgical specimens showed the predominance of small GABAergic inhibitory neurons exhibiting an intrinsic "pacemaker-like" behavior. 54 The concept that surgical intervention should mainly target the HH was not easy to accept.…”
Section: Pathophysiology: Intrinsic Epileptogenesis Of Hhsmentioning
confidence: 99%
“…Despite occasional suggestions of a cortical origin for this activity, surgical results based on these findings were uniformly poor (Cascino et al, 1993). The few cases with a good outcome for epilepsy were all submitted to surgical resection of the hamartoma (Nishio et al, 1989(Nishio et al, , 1994Valdueza et al, 1994;Rosenfeld et al, 2001;Palmini et al, 2002).…”
Section: Introductionmentioning
confidence: 99%